Novel roles for the MiTF/TFE family of transcription factors in organelle biogenesis, nutrient sensing, and energy homeostasis - Martina, José A. (Springer Basel, 2014)
The MiTF/TFE family of basic helix–loop–helix leucine zipper transcription factors includes MITF, TFEB, TFE3, and TFEC. The involvement of some family members in the development and proliferation of specific cell types, such as mast cells, osteoclasts, and melanocytes, is well established. Notably, recent evidence suggests that the MiTF/TFE family plays a critical role in organelle biogenesis, nutrient sensing, and energy metabolism. The MiTF/TFE family is also implicated in human disease. Mutations or aberrant expression of most MiTF/TFE family members has been linked to different types of cancer. At the same time, they have recently emerged as novel and very promising targets for the treatment of neurological and lysosomal diseases. The characterization of this fascinating family of transcription factors is greatly expanding our understanding of how cells synchronize environmental signals, such as nutrient availability, with gene expression, energy production, and cellular homeostasis.